Prevalence Rate of Depression among Ischemic Heart Diseases Patients in Al-Diwaneya Province / Iraq (Medico Legal Update, 2020)
Background: Cardiovascular disease is on the upraise in the industrialized and unindustrialized countries, which characterize at the present time one of the chief challenges for the health systems all the world. Depressed Ischemiac Heart disease patients may have a poorer outcome than non-depressed patients ,so this study was performed with the aim of finding the link between depression and ischemic heart disease and its association with demographic factors in Iraqi patients.Patients and Method: The study was designed to be a case- control study involving 128 case of IHD patients and120 apparently healthy individuals serving as control group, with an age range from 20y-80y in Al-Diwaniyah Teaching Hospital in Al-Diwaniyah province/ Iraq. were examined for the presence of depressive disorder using ICD-10 diagnostic criteria and then assessing the severity of the depression in the depressed group by using Beck Depressive Inventory(BDI ).Results: The prevalence rate of depression was 48.3% in IHD patients while 22.5% in control groups .Conclusion: Because of high rate of depression among patients with different types of heart diseases, early detection and identification of as possible ,to improve outcome .